Studi Sosiolinguistik tentang Jargon di Lingkungan Galangan Kapal Batam - Purba, Eydi Eyka Toto; Aldriani, Yessie (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2024)
Jargon is a variation of language used by certain communities to facilitate communication within the scope of their work. This study aims to analyze the use of jargon in the shipyard environment, especially in the field of mechanical engineering. It used a qualitative descriptive method with a sociolinguistics approach to identify and understand the meaning in communication in the shipyard industry. Data were collected through observation at PT Citra Shipyard Batam. The results show that there are 25 jargon terms used by workers in the shipyard, 11 words have different meanings between general and technical dictionaries, 6 words only have meaning in the field of engineering, and 8 words have the same meaning in both dictionaries. The use of this jargon facilitates communication between workers, improves work efficiency, and becomes part of their professional identity. However, for new workers, jargon can be a challenge. It indicates that jargon plays an important role in technical communication in shipyards.